Evaluasi Perencanaan Obat dan Perbekalan Farmasi di Depo Pusat Jantung Terpadu Rumah Sakit Umum Haji Adam Malik Medan - Ismedsyah Ismedsyah; Sri Rahayu (Jurnal Surya Medika (JSM), 2019)
Planning is an activity to determine the type and amount of medicine as needed. The weak plan is marked by the occurrence of emptiness or accumulation of drugs. The purpose of this study is to evaluate the medical planning and pharmacy supplies at Depo PJT RSUP HAM Medan period 2016-2017. The method of research is non-experimental research with a descriptive approach. Data collection used in this study is observations. Observations in question are analyzed records at Depo PJT RSUP HAM Medan 2016-2017. Research results show that the availability of funds in 2016 amounted to 102% and 2017 amounted to 101%; this has met the predetermined standard value of 100%. The percentage of absorption of funds provided in 2016 was 98%, and 2017 was 4.7%. The conclusion of this research show percentage availability funds in 2016 have been meet value standards that have been set in Regulation of the Minister of Health of Republic of Indonesia Number 72 of 2016. Deviations in Depo PJT planning RSUP Human Terrain 2016 and 2017 is still within the limit values limit deviation planning that is between 20-30%.